2021
DOI: 10.1038/s41467-021-24217-2
|View full text |Cite
|
Sign up to set email alerts
|

ATR regulates neuronal activity by modulating presynaptic firing

Abstract: Ataxia Telangiectasia and Rad3-related (ATR) protein, as a key DNA damage response (DDR) regulator, plays an essential function in response to replication stress and controls cell viability. Hypomorphic mutations of ATR cause the human ATR-Seckel syndrome, characterized by microcephaly and intellectual disability, which however suggests a yet unknown role for ATR in non-dividing cells. Here we show that ATR deletion in postmitotic neurons does not compromise brain development and formation; rather it enhances … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 96 publications
0
11
0
Order By: Relevance
“…Furthermore, although the MRN complex and ATR are all essential DDR molecules and the functions of the MRN complex also on upstream of ATR in the DDR pathway depending on cell cycle status and physiological status, deletion of Atr in Purkinje cells (Atr-PC mice) does not compromise the development and survival of Purkinje cells. However, Atr-PC mice show ataxia due to a defect of intrinsic neuronal activity mediated by modulating presynaptic firing through interacting between ATR and synaptotagmin 2 (SYT2), rather than cerebellar degeneration (Kirtay et al, 2021). In this regard, it is interesting to note that Purkinje cells from Mre11-deleted mice do not show any electrophysiological defects in the current study (Figure 6).…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…Furthermore, although the MRN complex and ATR are all essential DDR molecules and the functions of the MRN complex also on upstream of ATR in the DDR pathway depending on cell cycle status and physiological status, deletion of Atr in Purkinje cells (Atr-PC mice) does not compromise the development and survival of Purkinje cells. However, Atr-PC mice show ataxia due to a defect of intrinsic neuronal activity mediated by modulating presynaptic firing through interacting between ATR and synaptotagmin 2 (SYT2), rather than cerebellar degeneration (Kirtay et al, 2021). In this regard, it is interesting to note that Purkinje cells from Mre11-deleted mice do not show any electrophysiological defects in the current study (Figure 6).…”
Section: Discussionmentioning
confidence: 59%
“…Nbs1-PC or Mre11-PC mice with a specific deletion of Nbs1 or Mre11 in Purkinje cells were generated by crossing Nbs1 flox/flox (Frappart et al, 2005) or Mre11 flox/flox (Buis et al, 2008) mice with Pcp2-Cre transgenic mice (Kirtay et al, 2021). Nbs1-CNS ; P53-/-mice were generated previously described (Frappart et al, 2005).…”
Section: Mice and Genotypingmentioning
confidence: 99%
See 2 more Smart Citations
“…Reports of retinal malformations and degeneration have been found in Seckel and Nijmegen breakage syndrome ( Figure 1B ). However, possible non-canonical functions of RSR genes in post-mitotic cells should not be overlooked, as it has been recently shown that ATR-CHK1 pathway can have a direct function on post-mitotic neurons activity and regeneration in model organisms ( Kirtay et al, 2021 ; Li et al, 2021 ). Clinical investigations performing follow up in RSR-related syndromes patients associated with molecular diagnosis can bring important insights on the eye manifestations of these disorders.…”
Section: Discussionmentioning
confidence: 99%